An Economic Evaluation of Disallowing Body Checking in 11- to 12-Year-Old Ice Hockey Leagues. (March 2022) - Currie, Gillian R.; Lee, Raymond; Black, Amanda M.; Palacios-Derflingher, Luz; Hagel, Brent E.; Emery, Carolyn A.; Marshall, Deborah A.
Background: After a national policy change in 2013 disallowing body checking in Pee Wee ice hockey games, the rate of injury was reduced by 50% in Alberta. However, the effect on associated health care costs has not been examined previously. Hypothesis: A national policy removing body checking in Pee Wee (ages 11-12 years) ice hockey games will reduce injury rates, as well as costs. Study Design: Cost-effectiveness analysis alongside cohort study. Level of Evidence: Level 3. Methods: A cost-effectiveness analysis was conducted alongside a cohort study comparing rates of game injuries in Pee Wee hockey games in Alberta in a season when body checking was allowed (2011-2012) with a season when it was disallowed after a national policy change (2013-2014). The effectiveness measure was the rate of game injuries per 1000 player-hours. Costs were estimated based on associated health care use from both the publicly funded health care system and privately paid health care cost perspectives. Probabilistic sensitivity analysis was conducted using bootstrapping. Results: Disallowing body checking significantly reduced the rate of game injuries (−2.21; 95% CI [−3.12, −1.31] injuries per 1000 player-hours). We found no statistically significant difference in public health care system (−$83; 95% CI [−$386, $220]) or private health care costs (−$70; 95% CI [−$198, $57]) per 1000 player-hours. The probability that the policy of disallowing body checking was dominant (with both fewer injuries and lower costs) from the perspective of the public health care system and privately paid health care was 78% and 92%, respectively. Conclusion: Given the significant reduction in injuries, combined with lower public health care system and private costs in the large majority of iterations in the probabilistic sensitivity analysis, our findings support the policy change disallowing body checking in ice hockey in 11- and 12-year-old ice hockey leagues.